VIEWS INTO CONTEMPORARY NURSING - Savić, Nikola (Annals of Nursing, 2023)
Insights into Contemporary Nursing is a textbook for nursing students that sublimates all the knowledge that is the basis of good nursing education in an innovative and methodologically clear way. The textbook was published for the first time in 2023 and received good reviews from experts as well as reviewers. The textbook consists of 11 chapters: Chapter One: History of Nursing; Chapter Two: Definitions of Nursing and Health Care; Chapter Three: Theories and Models; Chapter Four: Quality of Health Care; Chapter Five: Organization, Safety, and Documentation; Chapter Six: Health Care Evidence-Based; Chapter Seven: The Health Care Process; Chapter eight: Nursing Ethics; Chapter Nine: Nursing Issues; Chapter Ten: Nursing Forensics; Chapter Eleven consists of appendices, scales, and instruments for practical application in nursing. The book is excellent literature for the education of various profiles of health workers, and it is extremely useful for the education of nurses.